Anemic Retinopathy with Subhyaloid Hemorrhage: Sinking the Boat with Laser - Kaustubh Rewatkar; Pratik Shenoy; Onkar H. Pirdankar; Amit S. Nene; Pushpanjali Badole; Smitesh Shah; Gaurav Kamble (Delhi Journal of Ophthalmology)
We report the case of a 37-year-old female diagnosed with subhyaloid hemorrhage (SHH) in her left eye due to anemia. She underwent Nd:YAG laser posterior hyaloidotomy for the SHH with its subsequent resolution over 1 month. Her best-corrected visual acuity improved from 20/1200 at presentation to 20/30 at 1-month follow-up. Postresolution, there were pigmentary changes at the macula which remained stable over a 9-month follow-up period.